The role of information and training for workers on the correct use of earplugs in assessing real noise attenuation with E-A-RfitTM system - Cassano, Filippo; Aloise, Ingrid; Labianca, Graziano; Gaccione, Vincenzo; Mazzotta, Cosimo; Cardascia, Francesco; Garavaglia, Michela; Germano, Candida; Dentamaro, Antonella; Di Lorenzo, Luigi (La Medicina del Lavoro, 2015)
Background: Laboratory levels of perceived noise attenuation as heard using earplugs are always higher than the real levels that can be achieved at the workplace. The employer is bound by law to supply individual hearing protection devices (HPDs), to assess their efficiency and efficacy, and also to inform and train workers on the correct use of HPDs. Objectives: This study assessed the real “personal attenuation rating” (PAR) of HPDs used by workers at the workplace, before (PAR A) and after (PAR B) specific and individual training. These values were also compared with the theoretical “single number rating” (SNR) provided by the manufacturer. Methods: The study covered all the 65 male employees of an awnings factory, using the E-A-RfitTM computerized method, which can measure PARs, based on the difference between sound pressures recorded by an “outside” microphone and an “inside” microphone placed in the auditory canal, with earplugs inserted, before (PAR A) and after (PAR B), i.e., the specific and individual training described above. Results/Conclusions: PARs B were always definitely higher than PARs A, both for all tested frequencies and the corresponding average values, which were automatically detected by E-A-RfitTM. Furthermore the same PARs B were decidedly lower than the respective SNRs supplied by the manufacturer on the basis of laboratory assessments. These data prove that specific and individual training for workers improves the performance of earplugs, contributing to a more appropriate secondary prevention of the effects of noise on hearing; they also prove that the real attenuation recorded in workers are always lower than those supplied by the manufacturer of the devices. It is recommended that the E-A-RfitTM system, which allowed these results to be achieved objectively, should be normally used to assess exposure to noise in workers, when HPDs are worn.